Synthetic Peptides and Peptidomimetics: From Basic Science to Biomedical Applications - Doti, Nunzianna; Ruvo, Menotti (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue, entitled "Synthetic Peptides and Peptidomimetics: From Basic Science to Biomedical Applications", has included both reviews and original research contributions focused on the chemical design and biomedical applications of structurally modified bioactive peptides. The papers collected show how successful this class of molecules still is, both as model molecules for studying the structure of proteins and as potential therapeutics and diagnostics, and also as laboratory tools for advanced basic and applied studies. The large scientific community working in this field is in fact very active and productive, and is making the most of the potential and versatility of these molecules to generate increasingly interesting and innovative molecules of therapeutic interest and to understand the fundamental molecular mechanisms of life.